The role of the general practitioner in the diagnostics of endocrine arterial hypertension - N. I. Volkova; I. Yu. Davidenko (Кардиоваскулярная терапия и профилактика, 2019)
Arterial hypertension (AH) is observed in almost every third of adult, and in 15% of cases it can be secondary. Endocrine hypertension as a cause of symptomatic hypertension (SAH) takes the second place after renovascular etiology. Thus, screening of endocrine SAH should be performed on almost every patient with AH. The general practitioner first meets a patient with elevated blood pressure levels, and his aim is to suspect SAH just-in-time, be able to provide its primary diagnostics, interpret the results and know the cases when patient with AH should be referred to a narrowly focused specialist. The article presents modern approaches to screening of endocrine hypertension causes, which allow not only to normalize blood pressure, but also to avoid complications.